Topographical Characteristics, Human Interactions, and Resource Boundaries in Tila Watershed, Nepal (The Geographic Base, 2023)
The geo-ecological fragility of rugged mountain topography with limited infrastructure development, and land capability constraints limit agriculture based livelihood options. The Tila Watershed of the Karnali region in Nepal with a high degree of fragility, marginality, and limited accessibility is no exception. A limited systematic analysis of dynamic interaction regarding land resources exists within the environmental (topography) and spatiotemporal (site distribution) contexts. This study explores the dynamic human environment interaction regarding land capability, and land resource utilization in traditional society vis-à-vis topographic limitations. An exploratory and analytical framework is adopted for assessing natural and human interrelationships. The primary data source includes Key Informant Interviews (KIIs) and informal discussions with locals from the study watershed. The secondary sources are mostly existing maps and derived products besides literature reviews. Land use change between 2000-2010, 2010-2019, and 2000-2019 show that the watershed has come under moderate pressure on forest and grassland while the built-up area has gradually increased. Among eight land cover classes, there is positive change (gain) in five classes and negative change in three classes. It is found that agriculture between 2000-2010 has shifted towards higher topographic and climatic constraints areas. Slope aspect and elevation are the determinants of diverse cropping patterns on two sides of the Tila River. There is a shift in agriculture patterns from more traditional subsistence farming towards commercial practice indicating adaptation to the agro-forestry-based agriculture system. Local policy and regulation play a vital role in promoting sustainable land use and agricultural practices. The study concludes that a dynamic adaptive approach based on proven traditional practices as evident in the Tila watershed and improvement and refinements in malpractices offers positive effects on both the environment and human life.